2017
DOI: 10.1111/sms.12865
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of contrast‐enhanced ultrasound in the diagnosis of plantar fasciitis

Abstract: Contrast-enhanced ultrasound (CEUS) is used to visualize the microvascularization in various tissues. The purpose of this study was to investigate whether CEUS could be used to visualize the microvascular volume (MV) in the plantar fascia, and to compare the method to clinical symptoms and B-mode ultrasound (US) in patients with plantar fasciitis (PF). Twenty patients with unilateral PF were included and were divided by US in insertional thickening (10), midsubstance thickening (5), and no US changes (5). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…However, studies have described an involvement of the heel pad in patients with plantar fasciitis. Using contrast‐enhanced US, increased blood flow in the fat pad has been noticed in feet with plantar fasciitis compared with healthy feet, which might affect the thickness of the fat pad . The shock‐absorbing capacity of the heel fat pad has also been found to change in feet with plantar fasciitis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have described an involvement of the heel pad in patients with plantar fasciitis. Using contrast‐enhanced US, increased blood flow in the fat pad has been noticed in feet with plantar fasciitis compared with healthy feet, which might affect the thickness of the fat pad . The shock‐absorbing capacity of the heel fat pad has also been found to change in feet with plantar fasciitis .…”
Section: Discussionmentioning
confidence: 99%
“…Using contrast-enhanced US, increased blood flow in the fat pad has been noticed in feet with plantar fasciitis compared with healthy feet, which might affect the thickness of the fat pad. 24 The shock-absorbing capacity of the heel fat pad has also been found to change in feet with plantar fasciitis. 25 In addition, Sabir et al 3 found a significant correlation between the thickness of the plantar fascia and the heel fat pad, but did not describe how these measurements were made.…”
Section: Us Of Heel Painmentioning
confidence: 99%
“…A single USG device (Philips EPIQ 5 L12-5 50 mm 12-5 MHz linear-array transducer, Philips Medical System, Andover, MA, USA) was used throughout the study by a single operator to measure the unloaded THPs and TFMFPs of all the patients. A method has been developed to take ultrasound measurements by reviewing previous studies 18, 19, 20. The patients were placed on the examination table in a prone position so that their feet were free outside the table.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol has been described in detail 13 . The subjects were instructed not to do any kind of rigorous exercise 24 h before the examination, and we required that the patients rested 30 min prior to the investigation.…”
Section: Methodsmentioning
confidence: 99%
“…The image analysis process is described in detail elsewhere 13 . The relative microvascular blood volume in the thickened part of the plantar fascia and in the heel fat pad separately was determined as the mean signal intensity in decibels (dB) during the first plateau phase after subtraction of the baseline levels (the mean signal intensity registered before the contrast bolus injection) 13 …”
Section: Methodsmentioning
confidence: 99%